PENGEMBANGAN WEBSITE SURABAYA DESIGN CENTER (STUDI KASUS TAMAN WISATA KAYOON SURABAYA) - Alifah, Amalia Nur; Rizky Fenaldo Maulana; Dominggo Bayu Baskara; Fajrul Falah Arrafi; Qothrunnadaa Nahdah Dzakiyyah; Ananda Taqhsya Dwiyana (Politeknik Negeri Sriwijaya, 2023)
In the ever-evolving digital era, the importance of digital marketing as a key tool in promoting businesses and services is increasingly apparent. The Kayoon area, which was originally the center of the decorative stone and jewelry trade in Surabaya, has experienced a decline in visits along with the impact of the COVID-19 pandemic. As a solution, the Surabaya City Government in collaboration with ADIDES and PK-KPBI ITS, along with ITTelkom Surabaya, initiated a revitalization by turning Kayoon into the Surabaya Design Centre (SDC). SDC aims to be an Urban Education area and a center for branding original handicraft products, but faces challenges in visibility and interaction in the digital era. To overcome this, a community service program is designed to assist SDC in improving the promotion of its business, products, and services digitally through website creation, social media, and Google Business registration. With the implementation of this digital marketing strategy, it is hoped that SDC can strengthen its reputation as a center of innovation and creativity, expand audience reach, and create new business opportunities within the design community. Thus, this community service program activity is expected to help the Kayoon community to get more benefits and new opportunities in this digital era.